How do you find critical points of multivariable function $f(x,y) = {x^3} + xy - {y^3}?$
Answer
Verified
438.9k+ views
Hint:First of all we will take the given expression and take differentiation with respect to “x” and “y” one by one and then find the factors and place the values of one variable to get the value for the other variable.
Complete step by step solution:
Take the given expression:
$f(x,y) = {x^3} + xy - {y^3}$
Differentiate the above expression with respect to “x”
\[\dfrac{d}{{dx}}f(x,y) = \dfrac{d}{{dx}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_x} = \dfrac{d}{{dx}}({x^3}) + \dfrac{d}{{dx}}(xy) - \dfrac{d}{{dx}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_x} = 3{x^2} + y\]
To find the critical value in the above equation equal to zero.
\[0 = 3{x^2} + y\] …. (A)
Similarly take derivative in the given expression with respect to “y”
\[\dfrac{d}{{dy}}f(x,y) = \dfrac{d}{{dy}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_y} = \dfrac{d}{{dy}}({x^3}) + \dfrac{d}{{dy}}(xy) - \dfrac{d}{{dy}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_y} = x - 3{y^2}\]
To find the critical value in the above equation equal to zero.
\[0 = x - 3{y^2}\] …. (B)
Take equation (A)
\[y = - 3{x^2}\]
Place the above value in the equation (B)
\[x - 3{( - 3{x^2})^2} = 0\]
Simplify the above equation-
\[x - 27{x^4} = 0\]
Finding the factors of the above equation.
$ \Rightarrow x(1 - 27{x^3}) = 0$
Implies
$x = 0$ …. (C)
or $1 - 27{x^3} = 0$
Simplify the above equation:
$1 = 27{x^3}$
When term multiplicative on one side is moved to the opposite side, then it goes to the
denominator.
$ \Rightarrow {x^3} = \dfrac{1}{{27}}$
Take a cube-root on both the sides of the equation.
$ \Rightarrow x = \dfrac{1}{3}$ …. (D)
Using the equation (C) and equation (A)
\[0 = 3{x^2} + y\]
Make “y” the subject, when any term is moved from one side to another the sign of the term also changes.
$y = - 3{x^2}$
Place $x = 0$
$ \Rightarrow y = - 3(0)$
Zero multiplied with anything gives zero.
$ \Rightarrow y = 0$ … (E)
Now, Place $x = \dfrac{1}{3}$ in equation (A)
$ \Rightarrow y = - \dfrac{1}{3}$
Hence, the critical points are: $(0,0)$ and $\left( {\dfrac{1}{3}, - \dfrac{1}{3}} \right)$
Note: Be careful about the sign convention when doing simplification. When you move any term from one side to another then the sign of the term also changes. Positive terms become negative and vice-versa.
Complete step by step solution:
Take the given expression:
$f(x,y) = {x^3} + xy - {y^3}$
Differentiate the above expression with respect to “x”
\[\dfrac{d}{{dx}}f(x,y) = \dfrac{d}{{dx}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_x} = \dfrac{d}{{dx}}({x^3}) + \dfrac{d}{{dx}}(xy) - \dfrac{d}{{dx}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_x} = 3{x^2} + y\]
To find the critical value in the above equation equal to zero.
\[0 = 3{x^2} + y\] …. (A)
Similarly take derivative in the given expression with respect to “y”
\[\dfrac{d}{{dy}}f(x,y) = \dfrac{d}{{dy}}({x^3} + xy - {y^3})\]
Apply differentiation to all the terms on the right hand side of the equation inside the bracket.
\[{f_y} = \dfrac{d}{{dy}}({x^3}) + \dfrac{d}{{dy}}(xy) - \dfrac{d}{{dy}}({y^3})\]
Apply the formula in the above equation and place the value in it.
\[{f_y} = x - 3{y^2}\]
To find the critical value in the above equation equal to zero.
\[0 = x - 3{y^2}\] …. (B)
Take equation (A)
\[y = - 3{x^2}\]
Place the above value in the equation (B)
\[x - 3{( - 3{x^2})^2} = 0\]
Simplify the above equation-
\[x - 27{x^4} = 0\]
Finding the factors of the above equation.
$ \Rightarrow x(1 - 27{x^3}) = 0$
Implies
$x = 0$ …. (C)
or $1 - 27{x^3} = 0$
Simplify the above equation:
$1 = 27{x^3}$
When term multiplicative on one side is moved to the opposite side, then it goes to the
denominator.
$ \Rightarrow {x^3} = \dfrac{1}{{27}}$
Take a cube-root on both the sides of the equation.
$ \Rightarrow x = \dfrac{1}{3}$ …. (D)
Using the equation (C) and equation (A)
\[0 = 3{x^2} + y\]
Make “y” the subject, when any term is moved from one side to another the sign of the term also changes.
$y = - 3{x^2}$
Place $x = 0$
$ \Rightarrow y = - 3(0)$
Zero multiplied with anything gives zero.
$ \Rightarrow y = 0$ … (E)
Now, Place $x = \dfrac{1}{3}$ in equation (A)
$ \Rightarrow y = - \dfrac{1}{3}$
Hence, the critical points are: $(0,0)$ and $\left( {\dfrac{1}{3}, - \dfrac{1}{3}} \right)$
Note: Be careful about the sign convention when doing simplification. When you move any term from one side to another then the sign of the term also changes. Positive terms become negative and vice-versa.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE